PENGARUH INTENSITAS PERSAINGAN PASAR TERHADAP KINERJA UNIT PERUSAHAAN: INFORMASI SISTEM AKUNTANSI MANAJEMEN SEBAGAI VARIABEL INTERVENING - ARFAN IKHSAN (Jurnal Bisnis dan Akuntansi, 2006)
The main objective of this study is to examine increasing in the market competition about the application of manufacturing technology, deregulation of economies and privatization of government owned enterprises makes decision makers tobe management accounting system information more important. There have been calls for research into the use of management accounting systems information under the changing circumstances. This research reports the results of a study which offers an explanation for the relationship between intensity of market competition and business unit performance by incorporating into the model the use of management accounting systems information by managers as intervening variable. To asses the relationship, data were collected from 36 manager product of manufacturing food and bavarages with responses rate result is 22,9%. The data determine by table sample size for a given population size who proposed Sekaran and the examine of the data by doing path analysis technique. The result of this research indicate that the intensity of market competition is a determinant of the use of the information MAS which, in turn, is a determinant plays a mediating role in the relationship between the intensity of market competitionand business unit performance. An interpretation of the result is that those organizations which use the information can effectively face competition in the market and thereby improve performance.